BERPIKIR KREATIF SISWA DILIHAT DARI VARIASI CARA PENYELESAIAN SOAL LUAS TRAPESIUM - Destya Renjani; Mohamad Rif'at; Dede Suratman (UNIVERSITAS TANJUNGPURA, 2022)
Creative thinking is one of the goals of national education, which means that every student is expected to develop it, so that students are accustomed to practicing their thinking skills to create new thoughts. Therefore, in solving problems students are expected to be able to use more than one way of solving. So, this study aims to describe students' creative thinking in variety ways of solving trapezoid area problems. Where students will solve trapezoid area problems using different solutions. The research method used is descriptive qualitative. The subjects in this study were 10 students of class VIII A SMP Negeri 9 Pontianak. The results showed that the overall average percentage of students in the variety of ways of solving the trapezoid area problem was in the fairly good category (50%). In fluency aspect, there are 7 (70%) students can meet the aspect and 3 (3%) students didn’t. In flexibility aspect, there are 6 (60%) students can meet the aspect and 4 (40%) students didn’t. In originality aspect, there are 2 (20%) students can meet the aspect and 8 (80%) students didn’t. In elaboration aspect, there are 5 (50%) students can meet the aspect and 5 (50%) students didn’t. Keywords: Creative thinking, Solve Problems using Different Solutions, Variety of Solutions